PROPHETESSES MAXIMILLA AND PRISCILLA WOMEN’S HERESIES IN THE PATRISTIC PERIOD - Edison R.L Tinambunan (Litbang STFT Widya Sasana Malang, 2018)
On his journey, the Church faces many heresies which try to deviate the orthodoxy teaching. One of these heresies was founded by Montanus and his teaching is known as Montanism. Montanus together with Maximilla and Priscilla claimed that they were filled by Holy Spirit and called themselves as a prophet and prophetesses who had to be followed and heard. The main teaching of this heresy is the promise of the second coming of Jesus Christ, and the promise of the end of the world. This theme is always interested by many people. The reason people attracted to the teaching of this heresy is the establishment of the coming of Jesus Christ which was promised by himself. Many of their followers became disappointed, because though the promised date had passed, Jesus Christ did not come yet. The other teaching of Montanism is about prophecy of the future which actually blinded the followers. If the prophecy failed to happen, it was because of the fault of the followers who lived less ascetic life and did many sins. The Prophets of Montanism had enthusiasm given by the Holy Spirit. It made them have to be obeyed and heard. They even claimed that the absolute truth was on their hand. Therefore, the hierarchy of the Church had to submit themselves to their teaching. Maximilla and Priscilla are two false prophetesses who had great influence in the Montanism period. In this heresy time, the Church had to work hard to fight Montanism teaching and prophecy, especially to defend its orthodoxy teaching of the Church from the false prophetesses. Sepanjang perjalanan, Gereja menghadapi banyak eresi yang berusaha mendefiasikan ajaran resmi. Salah satu di antara eresi yang banyak itu dikembangkan oleh Montanus yang alirannya dikenal dengan Montanisme. Ia bersama dengan Maximilla dan Priscilla mengaku kepenuhan Roh Kudus dan menyebut diri mereka sebagai Nabi yang harus diikuti dan didengarkan. Ajaran pokok mereka adalah menjanjikan kedatangan Kristus yang mau tidak mau juga menjanjikan akhir dunia yang biasanya diminati oleh banyak orang. Salah satu alasan ketertarikan orang lebih akan ajaran eresi ini adalah penetapan kedatangan Kristus yang dijanjika-Nya, walau akhirnya banyak orang menjadi kecewa, karena waktu yang ditetapkan tidak kunjung datang. Ajaran mereka lainnya adalah ramalan masa yang akan datang yang berusaha mengelabui pengikutnya. Jika ramalan tidak terpenuhi atau tidak kunjung datang, maka kesalahan berdada di tangan para pemohon karena kurang askese dan disposisi diri tidak baik. Para nabi ini memiliki sikap antusiasme berlebihan yang menekankan peran Roh Kudus yang mereka terima. Dengan alasan ini, mereka harus ditaati dan didengarkan. Bahkan kebenaran absolut berada di tangan mereka, bahkan pemimpin Gereja sendiri harus tunduk pada pengajaran mereka ini. Maximilla dan Priscilla adalah dua nabi perempuan yang sesat. Mereka sangat berpengarauh pada periode Montanisme. Gereja harus berjuang keras pada periode mereka untuk meluruskan ajaran dan ramalan Montanisme, terlebih membela ortodox Gereja dari nabi perempuan yang palsu tersebut.